2007
DOI: 10.1152/ajpregu.00284.2007
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for renal particulate and soluble guanylyl cyclases in preserving renal function in experimental acute heart failure

Abstract: . Distinct roles for renal particulate and soluble guanylyl cyclases in preserving renal function in experimental acute heart failure. Am J Physiol Regul Integr Comp Physiol 293: R1580-R1585, 2007. First published August 1, 2007; doi:10.1152/ajpregu.00284.2007.-Worsening renal function in the setting of human acute heart failure (AHF) predicts poor outcomes, such as rehospitalization and increased mortality. Understanding potential renoprotective mechanisms is warranted. The guanylate cyclase (GC) enzymes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…40 These two signalling systems are organized differently in terms of subcellular localization and mediate distinct physiological functions despite sharing the same second messenger. 41 In this regard, some studies [42][43][44] At any rate, RGZ treatment did not significantly increase excretory response to ACh infusion in CHF rats, while some improvement was observed in control rats. This aligns with a previous work from our laboratory showing blunted ACh-mediated renal vasodilatory response in rats with ACF, 25 suggesting that RGZ selectively improves signalling transduced by particulate GC rather than soluble GC.…”
Section: Discussionmentioning
confidence: 96%
“…40 These two signalling systems are organized differently in terms of subcellular localization and mediate distinct physiological functions despite sharing the same second messenger. 41 In this regard, some studies [42][43][44] At any rate, RGZ treatment did not significantly increase excretory response to ACh infusion in CHF rats, while some improvement was observed in control rats. This aligns with a previous work from our laboratory showing blunted ACh-mediated renal vasodilatory response in rats with ACF, 25 suggesting that RGZ selectively improves signalling transduced by particulate GC rather than soluble GC.…”
Section: Discussionmentioning
confidence: 96%
“…65,67 Different models of nephrectomy exist in mice, but these are not as robust as those in rats, with variable changes in renal function and cardiac abnormalities. [68][69][70][71][72] The renal hemodynamic response to heart failure (HF) induced by pacing in dogs has also been investigated, [73][74][75] but whether there is histological damage is unknown. Furthermore, there is no proven model of CKD in dogs.…”
Section: Previous Research On the Cardiorenal Interactionsmentioning
confidence: 99%
“…We hypothesized that each pathway would play specific roles in the control of kidney function in ADHF consistent with distinct GC enzymes for each system. (16) These studies revealed distinct roles for these two endogenous cGMP activating systems in ADHF whereby the endogenous NPs play a greater role in the preservation of GFR and sodium excretion while the endogenous NO system was more important in the control of renal blood flow. These studies suggest that the preservation of renal function in experimental ADHF is mediated by dual cGMP systems which activate both pGC and sGC enzymes.…”
Section: Acute Heart Failure and Cyclic Gmp Based Vasodilator Therapymentioning
confidence: 98%